The complex intracluster medium of Abell 1569 and its interaction with central radio galaxies - Tiwari, Juhi; Singh, Kulinder Pal (Oxford Academic, 2022)
We present the first in-depth study of X-ray emission from a nearby (z ∼ 0.0784) galaxy cluster Abell 1569 using an archival Chandra observation. A1569 consists of two unbound subclusters – a northern subcluster (A1569N) hosting a double-lobed radio galaxy 1233+169 at its centre, and a southern subcluster (A1569S) harbouring a wide-angle-tailed (WAT) radio source 1233+168. X-ray emission from A1569N and A1569S extends to a radius r ∼248 kpc and r ∼370 kpc, respectively, indicating that the two gas clumps are group-scale systems. The two subclusters have low X-ray luminosities (∼1042–43 erg s−1), average elemental abundances ∼1/4 Z⊙, low average temperatures (∼2 keV), and lack large (r ≳ 40–50 kpc) cool cores associated with the intracluster gas. We detect a pair of cavities coincident with the radio lobes of 1233+169 in A1569N. The total mechanical power associated with the cavity pair is an order of magnitude larger than the X-ray radiative loss in the cavity-occupied region, providing corroborating evidence for cavity-induced heating of the intragroup gas in A1569N. A1569S exhibits possible evidence for a small-scale cluster-subcluster merger, as indicated by its high central entropy, and the presence of local gas elongation and a density discontinuity in between the bent radio tails of 1233+168. The discontinuity is indicative of a weak merger shock with Mach Number, M ∼ 1.7. The most plausible geometry for the ongoing interaction is a head-on merger occurring between A1569S and a subcluster falling in from the west along the line bisecting the WAT tails.
Only IISER Mohali authors are available in the record.
Keywords: intracluster medium; Abell 1569; central radio galaxies